Breast milk supplementation and preterm infant development after hospital discharge: a randomized clinical trial - Roxana Desterro e Silva da Cunha; Fernando Lamy Filho; Eremita Val Rafael; Zeni Carvalho Lamy; André Luiz Guimarães de Queiroz (Elsevier, 2016)
Objectives: To assess the effect of maternal breast milk supplementation on the development of exclusively breast-fed very low birth weight preterm infants at 12 months of corrected age. Methods: A randomized clinical trial with 53 infants followed-up after discharge from the neonatal unit until a corrected gestational age of 12 months. Newborns in the intervention group were breastfed exclusively with maternal milk and received 2 g of a multinutrient supplement (Pré-Nan®, Nestlé, Vevey, Switzerland) added to expressed breast milk twice a day until a corrected age of 4-6 months. The control group was exclusively breastfed without supplementation. After monthly follow-up, developmental assessment was performed using the Bayley III Scale. Results: There was no statistically significant difference on the Bayley III Scale between the intervention and control groups in any of the assessed domains: motor, cognitive, and communication. However, scores in the three domains were always higher in the group that received the supplement. There were a similar number of cases of developmental delay in both groups: seven (28%) in the group that received the supplement and nine (33.3%) in the group that was exclusively breastfed. Conclusions: The results failed to show an association between post-discharge multinutrient supplementation and development in the assessed infants. Resumo: Objetivos: Avaliar o efeito da suplementação do aleitamento materno exclusivo com aditivo multicomponente no desenvolvimento de lactentes nascidos pré-termo de muito baixo peso aos 12 meses de idade gestacional corrigida. Método: Ensaio Clínico Randomizado com 53 lactentes, acompanhados da alta hospitalar na Unidade Neonatal até o 12° mês de idade gestacional corrigida. Aqueles alocados no grupo intervenção permaneciam em aleitamento materno exclusivo e recebiam 02 gramas de suplemento multicomponente em pó (Pré-Nan®, Nestlé, Vevey, Suíça), adicionados ao leite ordenhado duas vezes ao dia, por um período de 4 a 6 meses de idade gestacional corrigida. O grupo controle permanecia em aleitamento materno exclusivo sem suplementação. Após acompanhamento mensal, foi feita avaliação do desenvolvimento por meio da Escala de Bayley III. Resultados: Na comparação do desenvolvimento pela Escala de Bayley III entre os grupos intervenção e controle, não houve diferença estatística significante em nenhum dos domínios estudados: motor, cognitivo e linguagem. Porém, os valores dos escores foram sempre maiores no grupo intervenção que no grupo controle nos três domínios. O atraso de desenvolvimento se distribuiu de forma similar nos grupos: sete casos (28%) no grupo intervenção e nove (33,3%) no grupo controle. Conclusões: Os resultados não mostraram associação entre suplementação multicomponente pós-alta e o desenvolvimento dos lactentes analisados pela Escala de Bayley III. Keywords: Breastfeeding, Preterm, Hospital discharge, Development, Human milk, Palavras-chave: Amamentação, Prematuro, Alta hospitalar, Desenvolvimento, Leite Materno